RISK FACTORS FOR MALARIA INCIDENCE IN DISTRICT DIR LOWER KHAYBER PAKHTUNKHWA PAKISTAN (The Research of Medical Science Review, 2024)
This research shows that malaria is still a public health issue in District Dir Lower, Pakistan. This work aims to examine the seasonal distribution, demographic susceptibility, geographical prevalence, and other factors related to malaria epidemics of the past one year. Self-reported malaria was highest in July at 23.27% and lowest in December at 1.72%, based on data gathered between August of the previous year and July of the current year. It showed that malaria was highest in the monsoon season of July-August and reduced towards the last quarter of the year.The results also reveal that children 0-15 years had the highest proportion of malaria infections at 36.17% and the 31-45 years adults at 25.58%. Thus, the prevalence rate among the older adults (> 45 years) was observed to be relatively low (18.01%). These results show that malaria affects individuals belonging to a younger generation more than those of an older age. From the geographical point of view, Tehsil Khall had the highest percentage of Malaria positivity. It was 31.12%, the Tehsil Timergara 24.57%. Other districts like tehsil Balambat, tehsil Lal Qilla, and tehsil Adenzai had low rates of positives. These geographical differences imply the use of poverty-oriented malaria control measures in the affected regions. As seen earlier, there is a predominance of P. vivax with 85·15% compared with mixed infection with 14·85%. The use of an independent DT 139 shows that the control of malaria should now be based on species, and that Plasmodium vivax represents a major problem. Of the pregnant women, 53.45 % were infected with Plasmodium vivax; hence the need to address this populace. The study of cases by their category found that 40.78% of them were in patients under 15 years old and mostly had vivax malaria, while 17.72% were persistent. The fact that the cases have continued to manifest shows that transmission is still active and treatment, as well as control measures, should continue. The findings of risk factor analysis revealed that several factors predisposed people to malaria transmission. The history of travel within the last two weeks was established in 76.94% of patients hence travel is emerging as one of the main risks. Like the above results, outdoor activity (72.33%) and the presence of domesticated animals (88.76%) were found to correlate with a high prevalence of malaria. Moreover, the similar location, and specific items like the type of walls and ceiling at home also show the high possibility of being infected. In general, this study stresses some aspects of malaria epidemiology in District Dir Lower. The large fluctuations noted about seasonal, geographic, and demographic factors thus imply the need for finely tuned control and improved public health measures. Reduction of identified risk factors as well as enhanced surveillance will be imperative for excellent malaria care and reduction in the region.